Optimization of Repeater Spacing in Optical Fiber Communication (International Journal of Engineering and Computer Science, 2014)
Repeater spacing in fiber optic communication is optimized taking into consideration various parameters such as fiber attenuation, Stimulated Brillouin Scattering (SBS), Stimulated Raman Scattering (SRS), fiber attenuation, photodiode sensitivity and input power. In our work, we have taken different value of input power, change the different property of receiver as like APD Multiplier, different filter. Also, we have obtained results for various length of fiber and try to optimize the distance between two repeaters.